“Should I Stay or Should I Go?” : Prevalence and predictors of spatial mobility among youth in the transition to vocational education and training in Germany - Hoffmann, Linda [Verfasser]; Wicht, Alexandra [Verfasser] (My University, 2023)
“Spatial mobility is an important means of tackling regional disparities and matching problems in education and labor markets, but it is also a source of individual social inequality as it is associated with higher socio-economic resources and returns. However, there is a paucity of research on the prevalence and predictors of spatial mobility among youth entering vocational education and training (VET). We examine the importance of (a) individual occupational orientations, (b) regional opportunity structures, and (c) social ties for the spatial mobility of youth in this early transition phase using longitudinal data from the German NEPS, which we combined with administrative geospatial data of German districts (NUTS-3). Our results show widespread spatial mobility among students entering the VET system: 16% are mobile within and 22% between regional labor markets. Multinomial logistic regression models show that, in addition to young people’s occupational orientations (status aspirations; search duration) and social ties to friends, regional opportunity structures (general unattractiveness; person-environment mismatch) are crucial for youths’ spatial mobility. This underscores the importance of spatial mobility given regional disparities to promote youths’ access to VET and reduce regional mismatches in the VET market.” (authors’ abstract)
Keywords: P 1.1 Jugendliche; L 5 Beratung & Orientierung; G 1.3.2.2 Übergänge; G 1.3.3.3 Mobilität; 370; 300; Jugendlicher; Junger Erwachsener; Berufsorientierung; Berufseinmündung; Ausbildungsmobilität; Regionale Mobilität; Mobilitätsforschung; Regionale Disparität; Nationales Bildungspanel